(untitled) (History Journal «Jerónimo Zurita», 2022)
In the wake of Hitler and Mussolini’s Balkan campaign in April 1941, various resistance movements emerged in the bordering territories of Montenegro, Serbia, Bosnia, Croatia, Albania, Bulgaria, and Macedonia. Though based on different ideologies, one characteristic of these movements remained the same: They often consisted of transnational fighters acting in a transboundary manner. But collaborative movements also emerged, which exhibited transnational traits, too. Occupiers and collaborators—as well as resisters—were therefore confronted with a situation that was both geographically and socially perplexing; often neither borders nor affiliations were clearly defined. Because these phenomena appeared in a condensed way in the region of Sandžak and Kosovo border areas between all the above-mentioned states, I will focus on this part of Southeast Europe in the following article.